Limitation of activity and restriction of social participation in relation to age range, gender, and education in people with leprosy - Bianca Manzan Reis; Shamyr Sulyvan de Castro; Luciane Fernanda Rodrigues Martinho Fernandes (Sociedade Brasileira de Dermatologia, 2017)
Abstract Background: In Brazil, 38,000 new cases of leprosy are discovered each year, making it a public health problem. Objective: To identify whether or not there is an association between activity limitations and the restriction of social participation with some demographic data (age range, gender, and education) of the patients in a Basic Health Unit (BHU), diagnosed with leprosy. Methods: The SALSA scale was used to assess activity limitations, whereas the Participation scale was used to assess the restriction of social participation. Results: The assessments were conducted with 31 BHU patients diagnosed with leprosy. Males were the most affected by leprosy, the multibacillary was the most prevalent, and education proved to be an important factor when related to the disease injuries among the evaluated individuals. Regarding activity limitations and the restriction of social participation, the percentage of individuals without limitations and without restrictions was greater in both scales. Study limitations: The main limitation is the small study sample. Conclusion: It can be concluded that, for the studied sample, no association was observed between the activity limitations, evaluated by the Salsa scale, nor the restriction of social participation, evaluated by the Participation Scale, with the analyzed demographic data.